Learning for intercultural dialogue: concepts and strategies - Spajić-Vrkaš, Vedrana (2009)
Understanding that actions towards the different in one culture depends on the meaning the members of that culture attach to a specific difference that is proclaimed important in a particular historical context, makes the background upon which we intend to discuss the conceptual and strategic issues of learning for intercultural dialogue. In the paper we shall attempt to demonstrate that intercultural dialogue as a concept and a strategy has appeared only recently, particularly in the European political discourses, as a new solution to a long-lasting challenge of accommodating to the different ; that it is seen as a important tool for the integration and strengthening of culturally diverse democratic societies in a post-assimilation era in which profound changes in the normative conceptualisation of citizenship have been undertaken ; that its viability depends on what and how we both learn about and act towards our own and other cultures ; that such learning needs to be situated primarily in schools and universities in which it will be strengthened through transformative intercultural education programmes based on the principles of human rights, equality, active citizenship, cultural pluralism and social cohesion (‘unity in diversity’) ; and that the success of integration of such programmes in the European systems of education presupposes a series of complex changes ranging from reviewing the key educational concepts at the level of poliy, practice and theory to altering curricula and school organisation.